2018
DOI: 10.1007/s00784-018-2673-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age, gender, and time between blood draw and start of centrifugation on the size outcomes of platelet-rich fibrin (PRF) membranes

Abstract: Objectives Platelet-rich fibrin (PRF) has been utilized in regenerative dentistry as a supra-physiological concentrate of autologous growth factors capable of stimulating tissue regeneration. Due to the variability in the macroscopic morphology/size of PRF membranes observed between patients, we were interested in studying the effects of patient age, gender, and time between blood draw and the start of centrifugation on the size outcomes of PRF membranes. Despite PRF therapy being increasingly more popular in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 32 publications
5
52
0
4
Order By: Relevance
“…As erythrocytes and other blood components also play a role in coagulation, as well as the hematocrit counts vary between patients and affect the size of PRF membranes [20], the present study also showed that not only the total plasma volume but also the cellular content of the layers were altered (Supplemental Figures 1-3). We have previously shown that both females and patients above the age of 65 typically have larger membranes as a result of their lower hematocrit counts [20]. Future research is needed to better understand how centrifugation speed and time may be further optimized to result in similar final cell concentrations from patients with different starting blood cell counts.…”
Section: Discussionsupporting
confidence: 66%
“…As erythrocytes and other blood components also play a role in coagulation, as well as the hematocrit counts vary between patients and affect the size of PRF membranes [20], the present study also showed that not only the total plasma volume but also the cellular content of the layers were altered (Supplemental Figures 1-3). We have previously shown that both females and patients above the age of 65 typically have larger membranes as a result of their lower hematocrit counts [20]. Future research is needed to better understand how centrifugation speed and time may be further optimized to result in similar final cell concentrations from patients with different starting blood cell counts.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, there was also variability reported between patients. As the hematocrit counts vary between patients and affect the size of PRF membranes [20], the present study also showed that not only the total plasma volume but also the cellular content of the layers were altered (Supplemental Figs. 1-3).…”
Section: Discussionsupporting
confidence: 67%
“…1-3). We have previously shown that both females and patients above the age of 65 typically have larger membranes as a result of their lower hematocrit counts [20]. Future research is needed to better understand how centrifugation speed and time may be further optimized to result in similar final cell concentrations from patients with different starting blood cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…Activated clotting time is usually around 2 min [ 17 ]; thus, the coagulation is rapidly advancing even before the tubes are exposed to centrifugation forces. Usually, the recommended time between the blood drawing and start of centrifugation is 60–90 s; otherwise the size of the PRF membrane is negatively affected [ 18 ]. Noteworthy, it is not only the size of the PRF membrane that matters but attention has also been paid to the distribution of platelets within the PRF membranes [ 8 ], as platelets are rapidly activated during the coagulation cascade and thereby entrapped in the developing fibrin-rich extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%